Acute toxicity of synthetic pyrethroid cypermethrin on the common carp (Cyprinus carpio L.) embryos and larvae - Aydin, R; Köprücü, K; Dörücü, M; Köprücü, SS; Pala, M (Springer, 2005)
In this study, the toxic effects on the embryos and larvae of the common carp were used as a model to investigate the synthetic pyrethroid pesticide, cypermethrin, which contaminates aquatic ecosystems. Data obtained from the cypermethrin acute toxicity tests were evaluated using the Probit Analysis Statistical Method. The control and eight test experiments were repeated five times. The number of dead embryos significantly increased in response to cypermethrin concentrations 0.0001, 0.001, 0.01, 0.1, 1, 2, 4 and 8 mu g l(-1) ( p< 0.05 for each case). The 48 h LC50 value ( with 95% confidence limits) of cypermethrin for common carp embryos was estimated at 0.909 (0.256 - 5.074) mu g l(-1). Dose - response decreases in hatching success were recorded as 87.4, 85.0, 80.2, 71.4, 56.3, 48.6, 38.8 and 23.5%, respectively. The lowest concentration of cypermethrin (0.0001 mu g l(-1)) produced a significant increase in the number of dead larvae compared to the control group ( p< 0.05). The number of dead larvae significantly increased with increasing cypermethrin concentrations exposed for 1 - 96 h ( p< 0.05). The highest concentration ( 8 mu g l(-1)) showed the highest larvae mortality. The 96 h LC50 value (with 95% confidence limits) of cypermethrin for common carp larvae was estimated at 0.809 (0.530 - 1.308) mu g l(-1). The results of the study suggest that low levels of cypermethrin in the aquatic environment may have a significant effect on the reproduction and development of carp.
Keywords: acute toxicity; common carp; cypermethrin; Cyprinus carpio; embryo; hatching success; larvae; synthetic pyrethroid